1999
DOI: 10.1128/iai.67.12.6286-6292.1999
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Monosaccharide Lipid A Analogues in Human Monocytic Cells as Agonists or Antagonists of Bacterial Lipopolysaccharide

Abstract: The lipid A portion of bacterial lipopolysaccharide (LPS) plays a central role in the production of endotoxic mediators. Different responses between human and murine macrophages to lipid A-like structures have been indicated. We investigated a series of structurally related monosaccharide lipid A analogues for their potency to activate human macrophage U937 cells and peripheral blood mononuclear cells for production of tumor necrosis factor-␣ and interleukin-6 compared with their potency to activate murine mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 37 publications
1
31
0
Order By: Relevance
“…These fall in two broad categories: receptor antagonists and LPS-neutralizing molecules. Among the fi rst are LPS-like molecules isolated from bacteria (Rhodobacter capsulatus and sphaeroides, Porphyromonas gingivalis, and Helicobacter pylori), deacylated LPS, lipid IVa, synthetic Lipid A analogues (including E5531, E5564, DT-5461, and GLA-47), and certain cationic peptides (40)(41)(42)(43)(44)(45)(46)(47)(48)(49). LPS-neutralizing molecules include polymixin B and synthetic peptides (50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…These fall in two broad categories: receptor antagonists and LPS-neutralizing molecules. Among the fi rst are LPS-like molecules isolated from bacteria (Rhodobacter capsulatus and sphaeroides, Porphyromonas gingivalis, and Helicobacter pylori), deacylated LPS, lipid IVa, synthetic Lipid A analogues (including E5531, E5564, DT-5461, and GLA-47), and certain cationic peptides (40)(41)(42)(43)(44)(45)(46)(47)(48)(49). LPS-neutralizing molecules include polymixin B and synthetic peptides (50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…[65,66] Studies of the biological activities of monosaccharide-type lipid A analogues have identified the most agonistic character attributed to the tri-acylated lipid A partial structure, which is monophosphorylated at the C4 position and acylated by C14:0(3-OH) at the C3 and C2 positions with a branched C12:0 connected to the ester-linked primary fatty acid. [67][68][69] In all samples, the predominant species with the highest chromatographic peak was the hexa-acylated monophosphorylated lipid A at m/z 1716. The area of this peak was used to quantitate the lipid A mixtures.…”
Section: Component Distribution and Origin Of Heterogeneitymentioning
confidence: 95%
“…Mouse and human macrophage cell lines, RAW264.7 (from the American Type Culture Collections, Rockville, MD, USA) and U937 (from the Japanese Cancer Research Resources Bank, Tokyo, Japan), respectively, were used as target macrophages for activation. Cells were cultured and stimulated as described in the previous papers [11,12]. Tumor necrosis factor (TNF) production in the culture supernatant was measured by a cytotoxic assay against L-929 cells [13].…”
Section: Macrophage Activation Activitymentioning
confidence: 99%